2020
DOI: 10.1101/2020.09.30.20204644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of novel coronavirus (covid-19) reproduction number and case fatality rate: a systematic review and meta-analysis

Abstract: Understanding the transmission dynamics and the severity of the novel coronavirus disease 2019 (COVID-19) informs public health interventions, surveillance, and planning. Two important parameters, the basic reproduction number (R0) and case fatality rate (CFR) of COVID-19, help in this understanding process. The objective of this study was to estimate the R0 and CFR of COVID-19 and assess whether the parameters vary in different regions of the world. We carried out a systematic review to retrieve the published… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 100 publications
1
22
3
1
Order By: Relevance
“…This is among the first studies to evaluate multiple simultaneous clinical data streams with an epidemic transmission model. The symptomatic case fatality ratios (sCFR) inferred for RI, PA, and MA (estimates range from 2.5% and 3.7%) are in the higher ranges of previously reported estimates [8][9][10][11][53][54][55], suggesting that the individuals infected during the spring wave and summer lull were more likely to progress to symptoms than the average person in the population. Again, this is consistent with the observation that children were the least exposed in the spring and summer months, and thus the exposed population was both more likely to progress to reportable symptoms and more likely to progress to severe clinical outcomes.…”
Section: Discussionmentioning
confidence: 69%
“…This is among the first studies to evaluate multiple simultaneous clinical data streams with an epidemic transmission model. The symptomatic case fatality ratios (sCFR) inferred for RI, PA, and MA (estimates range from 2.5% and 3.7%) are in the higher ranges of previously reported estimates [8][9][10][11][53][54][55], suggesting that the individuals infected during the spring wave and summer lull were more likely to progress to symptoms than the average person in the population. Again, this is consistent with the observation that children were the least exposed in the spring and summer months, and thus the exposed population was both more likely to progress to reportable symptoms and more likely to progress to severe clinical outcomes.…”
Section: Discussionmentioning
confidence: 69%
“…In agreement with previous studies [29,30], our estimated CFRs for selected countries were lower than most of the European countries' CFR. Several factors, such as temperature, the proportion of young people, genetic factors, can be responsible for this variation in CFR [12,14,[31][32][33]. Moreover, we found that CFR of the COVID-19 pandemic is less than SARS, MERS, Bird flu, and Ebola [34,35].…”
Section: Discussionmentioning
confidence: 92%
“…As a result, in the first 10 days since the imposition of test fees, there had been a decrease of 8,736 tests in total from the previous 10-day period. More tests can detect more asymptomatic or mild cases, which reduced the mortality rate [12,14]. However, as the decision had affected the poor citizen's ability or willingness of testing [18], the Bangladesh government decided to cut the test fees by almost half on 20 August [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations